Acceptance and Willingness to Pay for Cardiovascular Disease Screening: A Systematic Review - Amalia Hanifti Choirunisa; Susi Ari Kristina; Nanang Munif Yasin (Generics: Journal of Research in Pharmacy, 2026)
Cardiovascular Disease (CVD) ranks as the highest economic burden; many individuals remain undiagnosed due to the absence of a structured screening program or lack of early-stage treatment. Willingness to Pay (WTP) is a method used to assess consumers' preference for a product or service by evaluating their financial capacity and willingness to pay within a given population. This systematic review aimed to examine studies of WTP and factors influencing CVD screening. The required articles were collected by searching for relevant keywords in PubMed, Scopus, and Google Scholar. This systematic review was conducted using the PRISMA method. Seven studies were included in the review. Most participants were aged above 55 years, and 50% were diagnosed with early-stage hypertension. The WTP ranged from US$ 10 to US$ 500 per annual screening test. The results of reviewed studies indicate a relatively high level of acceptance for CVD screening. Family history and perception of risk are the most significant factors, besides cost. These findings can serve as a valuable reference for policymakers in implementing effective public health interventions. By developing and promoting screening programs, governments can enhance preventive measures to reduce the morbidity and mortality associated with CVD.